Do Elderly Patients With Stage I–II Hepatocellular Carcinoma Benefit From More Radical Surgeries? A Population-Based Analysis - Zhang, Qiu-Qiang; Wu, Pan-Yi-Sha; ALBahde, Mugahed; Zhang, Lu-Fei; Zhou, Zhu-Ha; Liu, Hua; Li, Yu-Feng; Wang, Wei-Lin (Frontiers in Oncology, 2020)
Abstract Background & Aims: The best treatment modality is always controversial, on an era of a shortage of liver donors, for the elderly patients with stage I–II HCC(hepatocellular carcinoma). Methods: From SEER database(Surveillance, Epidemiology, and End Results program), 2,371 elderly patients were sampled as Cohort 1. OS(Overall Survival) and CSS(Cancer Specific Survival) were compared between the Non-surgery and Surgery groups. A stratification analysis in CSS Cox model was also conducted among sub-groups. Propensity Score Matching was also performed to generate Cohort 2(746 pairs), reducing the influences of confounders. Results: For Cohort 1, the median follow-up times of Non-surgery and Surgery groups were 11 months(95%CI, confidence interval: 9.74-12.26) versus 49 months(44.80-53.21) in OS, and 14 months(12.33-15.67) versus 74 months(64.74-83.26) in CSS respectively. In the stratification analysis, for the elderly patients(age>=70 years), the Larger Resection was associated with higher HR(hazard ratio) than the Segmental Resection: 0.30(95%CI, confidence interval: 0.22-0.41) VS. 0.29(0.21-0.38) in 70-74 years; 0.26(0.18-0.38) VS. 0.23(0.16-0.32) in 75-79 years; 0.32(0.21-0.49) VS. 0.21(0.13-0.32) in 80+ years. For Cohort 2, the similar result could be seen in the CSS Cox forest plot. The HR of LR and SR was 0.27(0.21-0.33) and 0.25(0.20-0.31) respectively. Conclusions: Based on the SEER data, It may be cautiously recommended that compared with other surgeries when liver transplantation is not available, segmental or wedge liver resection should be the best treatment choice for the elderly patients with stage I–II HCC(AJCC edtion 6), especially those who are >=70 years.